4-Field Symmetry Breakings in Microresonator-Based Photonic Molecules - Ghosh, Alekhya; Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Spontaneous symmetry breaking (SSB) is said to have occurred when two or more properties of a system suddenly change from having equality between them (symmetric) to having an inequality (asymmetric) following an infinitely small change to some system parameter. Recently there has been rapid growth of research on SSB in Kerr resonators, for examples, between two counterpropagating light fields [1], and two orthogonally polarized modes [2]. In this work [3], we describe novel mechanisms for SSB, which cause four field symmetry breakings [4] in two different photonic molecule structures (two coupled ring resonators) with different field coupling mechanisms.
CRIS-Team Scopus Importer:2024-12-16